IMM-H007, a novel small molecule inhibitor for atherosclerosis, represses endothelium inflammation by regulating the activity of NF-κB and JNK/AP1 signaling - Yu, Jinjin; Ming, Hong; Li, Henry You; Yu, Bin; Chu, Maoping; Zhu, Haibo; Zhu, Xinxing (Toxicology and applied pharmacology, 2019)
Endothelium inflammation has become a major risk factor for pathological development of atherosclerosis. IMM-H007 (H007), a small molecule compound, is previously reported to reduce inflammatory atherosclerosis. However, the regulatory role of H007 in endothelium inflammation is still unclear. Here, we characterize H007 as a critical repressor in regulation of endothelium inflammation. We find that H007 significantly inhibits monocyte adhesion to endothelial cells and its transendothelial migration. Mechanistically, H007 markedly represses TNFα-induced IκBα degradation and NF-κB nuclear translocation, therefore leading to NF-κB-mediated inflammatory suppression. Moreover, another inflammatory signaling JNK/c-Jun, which is always co-activated with NF-κB in response to pro-inflammatory stimuli, is also found to be restrained by H007 through reducing its phosphorylation status. Thus, we conclude that H007 negatively regulates endothelium inflammation through inactivating NF-κB and JNK/AP1 signaling. More importantly, this study provides us a new insight into understanding the molecular basis by which H007 regulates inflammatory atherosclerosis. [Display omitted] •H007 negatively regulates endothelium inflammation.•H007 regulates NF-κB signaling by repressing proteasome-mediated IκBα degradation.•H007 regulates JNK/c-Jun signaling through restraining its phosphorylation status.